A model for the incorporation of the environmental education for the sustainable development to the pedagogic process - Moré Estupiñán, Mavel; Evora Larios, Onelia E.; García García, Tania; Sánchez Correa, Anais (Avances en Supervisión Educativa, 2016)
The insufficient attention to the incorporation of the environmental education for the sustainable development to the pedagogic process in the different subsystems of the National System of Education of the county of Villa Clara, this becomes the motive of the present study. In the investigation detailed the process that drives to the construction of a model for the incorporation of the environmental education for the sustainable development to the pedagogic process in the different subsystems of the National System of Education, presently of the county of Villa Clara. This constitutes a modest contribution to the execution of an action of the National Strategy of Environmental Education, 2010-2015, related with the construction of a theoretical-methodological model for the environmental education in Cuba.
Keywords: environmental education for the sustainable development; pedagogic process; National System of Education; model; systematizing of experiences